NURSES PERCEPTION OF WORKPLACE VIOLENCE & ASSOCIATED COPING STRATEGIES (The Research of Medical Science Review, 2025)
Background: Workplace violence (WPV) is a critical global issue in healthcare, disproportionately affecting nurses who serve on the frontlines of patient care. Exposure to physical, verbal, and psychological violence undermines nurses' well- being, job satisfaction, and overall care quality Objective: This study aimed to explore nurses’ perceptions of workplace violence and examine the coping strategies they employ in response to such incidents in two hospitals located in Sindh, Pakistan. Methods: A descriptive cross-sectional study was conducted with a sample of 45 registered nurses from District Hospital Sanghar and Taluka Hospital sanjhoro. Data were collected using a structured questionnaire and analyzed using SPSS version 16 to determine frequencies and descriptive statistics related to the prevalence, sources, and impacts of WPV. Results: Findings revealed that 77.8% of nurses reported experiencing workplace violence at least "rarely," with verbal abuse being the most frequently encountered form (82.2%). The primary perpetrators were patients’ relatives (66.7%). Almost half of the respondents (48.9%) chose to ignore the violence, and only 24.4% reported the incidents. Despite 62.2% of incidents being formally investigated, just over half (51.1%) expressed satisfaction with the institutional response. WPV had a moderate to severe impact on job performance for 51.1% of nurses, while fear of retaliation remained a significant barrier to reporting. Conclusion: Workplace violence is a prevalent and underreported issue among nurses in the selected healthcare settings. Most incidents involve verbal abuse by patient attendants, with limited institutional support perceived by affected staff. Strengthening workplace safety policies, enhancing incident reporting systems, and providing psychological support are essential to creating a safer and more supportive work environment for nurses.